Option B : Facing Adversity, Building Resilience, and Finding Joy - Sandberg, Sheryl and Grant, Adam (London WH Allen, 2017)
"From Facebook's COO and Wharton's top-rated professor, the #1 New York Times best-selling authors of Lean In and Originals: a powerful, inspiring, and practical book about building resilience and moving forward after life's inevitable setbacks. After the sudden death of her husband, Sheryl Sandberg felt certain that she and her children would never feel pure joy again. "I was in 'the void, '" she writes, "a vast
Include Illustrations, Notes and Index
Keywords: Loss (Psychology) -- Resilience (Personality trait) -- Bereavement